Pengaruh Imbangan Daging Ayam (Gallus gallus domesticus) dan Jamur Tiram Putih (Pleurotus ostreatus) Terhadap Karakteristik Nugget Yang Dihasilkan - Imas Santiah Santiah; Kelik Putranto (Ma'soem University, 2026)
Nuggets are a type of food product that is popular with the public because of its practical nature. Generally made from chicken meat. Innovation in this product includes the addition of white oyster mushrooms to increase the diversification of high-fiber nugget processing. The purpose of this study was to obtain the right balance of chicken meat and white oyster mushrooms to produce the best nugget characteristics. This study was conducted in the Chemistry Laboratory and Food Processing Laboratory of the Faculty of Agriculture, Ma'soem University and chemical testing was carried out in the West Java Provincial Health Laboratory from April to June 2025. The study used a Randomized Block Design (RBD) with six treatments of chicken meat and white oyster mushrooms (100:0, 90:10, 80:20, 70:30, 60:40 and 50:50) and four replications. The observed characteristic parameters were water content, protein content, fat content, crude fiber content as well as organoleptic tests in the form of color, aroma, taste and texture. The results of this study indicate that the balance of chicken meat and white oyster mushrooms 80:20 produces nuggets with the best characteristics. This determination is based on water content 54.20%, protein content 24.16%, fat content 5.82%, crude fiber content 6.05% and organoleptic tests of color 3.56 (like), aroma 3.35 (like), taste 3.77 (like) and texture 3.61 (like).